Appraisal of electromagnetic induction effects on magnetic pulsation studies - Arora, B.R.; Subbarao, P.B.V.; Trivedi, N.B.; Padilha, A.L.; Vitorello, I. (My University, 2001)
The quantification of wave polarization characteristics of ULF waves from the geomagnetic field variations is done under ‘a priori’ assumption that fields of internal induced currents are in-phase with the external inducing fields. Such approximation is invalidated in the regions marked by large lateral conductivity variations that perturb the flow pattern of induced currents. The amplitude and phase changes that these perturbations produce, in the resultant fields at the Earth’s surface, make determination of polarization and phase of the oscillating external signals problematic. In this paper, with the help of a classical Pc5 magnetic pulsation event of 24 March 1991, recorded by dense network of magnetometers in the equatorial belt of Brazil, we document the nature and extent of the possible influence of anomalous induction effects in the wave polarization of ULF waves. The presence of anomalous induction effects at selected sites lead to an over estimation of the equatorial enhancement at pulsation period and also suggest changes in the azimuth of ULF waves as they propagate through the equatorial electrojet. Through numerical calculations, it is shown that anomalous horizontal fields, that result from induction in the lateral conductivity distribution in the study region, vary in magnitude and phase with the polarization of external source field. Essentially, the induction response is also a function of the period of external inducing source field. It is further shown that when anomalous induction fields corresponding to the magnitude and polarization of the 24 March 1991 pulsation event are eliminated from observed fields, corrected amplitude in the X and Y horizontal components allows for true characterisation of ULF wave parameters.
Keywords: Geomagnetism; Ionosphere; Magnetospheric physics; ULF waves; Magnetic pulsation studies; Paleomagnetism